The clinical effect of an electric massage chair on chemotherapy-induced nausea and vomiting in cancer patients: randomized phase II cross-over trial - Ju Won Kim; Ah Reum Lim; Ji Yoon Lee; June Young Lee; Soohyeon Lee; Yoon Ji Choi; Yeol Hong Kim; Kyong Hwa Park (BMC, 2024)
Abstract Purpose Chemotherapy-induced nausea and vomiting (CINV) is a common adverse events in cancer patients and can negatively affect their quality of life (QoL). This study aimed to evaluate the clinical efficacy of an electric massage chair (EMC) for the treatment of CINV. Methods A randomized phase II cross-over trial was conducted on solid cancer patients who received moderate (MEC) to high emetogenic chemotherapy (HEC). The participants were randomly assigned to receive their first chemotherapy either on a standard bed (Group A) or in an EMC (Group B) during the infusion. The patients were then crossed over to the next cycle. CINV and QoL questionnaires were collected from the participants. Results A total of 59 patients completed the trial protocol and were included in the analysis, with 29 and 30 patients in Groups A and B, respectively. The mean INVR (Index of Nausea, Vomiting, and Retching) score in the 2nd day of the first cycle was higher in Group B (3.63 ± 5.35) than Group A (2.76 ± 4.78), but the difference was not statistically significant (p = 0.5367). The complete response rate showed little difference between the groups. Among the high-emetic risk subgroups, patients who received HEC (p = 0.04595), younger patients (p = 0.0108), and non-colorectal cancer patients (p = 0.0495) presented significantly lower CINV scores when EMC was applied. Conclusion Overall, there was no significant difference in INVR scores between standard care and EMC. Applying EMC at the first chemotherapy infusion may help preserve QoL and reduce CINV in high-risk patients. Trial registration KCT0008200, 17/02/2023, Retrospectively registered.